The National Endowment for the Humanities : un levier fédéral des musées amérindiens - Gérard Selbach (Revue LISA)
The National Endowment for the Humanities (NEH) is a federal agency created in 1965 with the mission of “serving the nation by promoting the humanities and giving lessons of history to all Americans.” It finances radio and TV programs on history, music and industry as well as interpretative museum exhibitions and the publishing of catalogs. This article aims at studying one specific type of grant aimed at museums and at exploring the way the compliance with the criteria set by the NEH may affect the organization and contents of exhibitions of tribal museums in particular. It wonders whether the fact of imposing outside scholars (i.e. non-Indian experts) is not a means of controlling the interpretation of Native American history and of disguising and furthering the government’s policy of assimilation into the mainstream.